INDIGENOUS PEOPLES, HUMAN RIGHTS, AND EDUCATION (Social and Environmental Law Journal, 2024)
Brief Biography:In addition to being a Permanent Professor in the Graduate Program in Constitutional Law at the Federal University of Ceará (UFC), a Collaborating Professor in the Graduate Program in Law and Society in Latin America and the Caribbean (LATAM) at São Paulo State University (UNESP), and a Visiting Researcher at the Center for Social Studies (CES) of the University of Coimbra, Portugal, Mariana Silva is a senior researcher at the Institute of Advanced Legal Studies (IEJA) in Brasília, Brazil. Her research explores the intersection between human rights and territories, addressing topics such as the protection of territorial rights for indigenous and quilombola communities, the challenges in implementing sustainable development policies, and legal education practices in traditional communities. Professor Mariana has collaborated with the International Human Rights Network, participating in global and regional processes related to the protection of vulnerable communities' rights and climate justice. With internationally recognized contributions, she has been involved in creating human rights training initiatives for indigenous and rural communities and in collaborative teaching projects in countries like Colombia, Mexico, Portugal, Mozambique, Argentina, and Ecuador.